The study of the drying kinetic and the cutting performance in dried betel nut production machine - Naruebodee Srisang; Siriwan Srisang; Thatchapol Chungcharoen (My University, 2018)
Betel nut kernel is an important raw material in the leather and dye industries. The quality control after harvest is necessary, especially, the excess moisture content may cause the spoilage. Therefore, this research aims to study the betel nut fruit drying using infrared ray combined with the rotated trays. The betel nuts fruits were placed in rotated trays. These trays were installed within drying chamber which had the infrared rod in 2 positions namely the center and wall of drying chamber. The drying temperature used at 80, 100 and 120°C. The revolution speed of tray was set at 2, 4 and 6 rpm. The dried betel nut fruits were cut into 2 pieces at the blade speed of 25, 30 and 35 rpm. The experimental results showed the installation of infrared rods at the center could decrease the moisture content faster than at the wall. The betel nut fruit should use the drying temperature of 120°C for 10 h and the revolution speed of 2 rpm. The blade speed of 30 rpm gave the most cutting performance about 76%. The colour of dried betel nut kernel (L * , a * and b * ) did not significantly difference with the commercial betel nut.
Keywords: Betel; Tray; Nuts composition and effects